Saudi Undergraduate EFL Learners' Listening Strategies - Al-shehri, Yasmeen; Alhamami, Munassir (Fakultas Sastra - Universitas Muslim Indonesia, 2023)
Listening comprehension is a critical skill for English as a foreign language (EFL) learners, and it is particularly challenging for Saudi EFL learners due to the differences between Arabic and English phonology. This study investigated the listening strategies used by EFL learners. The Listening Comprehension Strategy Inventory (LCSI) was administered to 73 Saudi EFL learners in a Saudi public university. The survey was divided into three sections: metacognitive, cognitive, and socio-affective strategies. The results showed that the most commonly used listening strategies in each category were: Metacognitive strategies: using prior knowledge and experience to help understand, predicting what will be said, and checking understanding. Cognitive strategies: focusing on key words, repeating words to become familiar with sounds, and using context clues; and Socio-affective strategies: developing a positive attitude towards listening, and believing that it is possible to understand what will be heard. comparing the results of the three constructs show that participants had the highest mean scores for cognitive strategies, followed by metacognitive strategies, and then socio-affective strategies. The results suggest that Saudi EFL learners use a variety of listening strategies. This study contributes to the field by providing new insights into the listening strategies used by Saudi EFL learners.